Dede Eri Supria's Creative Process of Painting Marginaled Urban People in the New Order Era - Ramdani, Guruh; Tambunan, Shuri Mariasih Gietty; M, Yoesoef; Tommy, Christomy (Mudra Jurnal Seni Budaya, 2024)
This article aims to reveal the creative process of Dede Eri Supria (DES) in the context of the development of Indonesian painting, showing the structure, style and thematics that represent the impact of development policies and New Order cultural politics. The discussion of this creative process uses Gramsci's concept of hegemony, namely the dominant group's ideology, to perpetuate its power through its apparatus spread throughout civil society, most of which are intellectual groups. This ideological hegemony also occurred in Indonesian painting during the New Order era. This article uses a qualitative description method to reveal and discuss data obtained through interviews and literature studies. Based on these methods and concepts, the following results were obtained. First, DES's creativity was influenced by his social environment with exponents of the New Fine Arts Movement (GSRB), which resulted in his critical views on social and cultural problems and ideological problems in the creative environment of ASRI students and GSRB activists. Second, the DES creative process is a creative reaction to express "freedom" in work to fight the dominant ideology that dominates art. Third, through a creative space free from dominant art ideologies, DES and GSRB exponents display their works at the TIM GSRB Exhibition. Fourth, the social, cultural and political development conditions during the New Order era impacted the socio-economic lives of marginalized urbanites, becoming one of the stimuli for the DES creative process. Fifth, DES in painting uses various visual references but does not copy them outright and creates a new reality in the space of his canvas so that his paintings represent a new type of art that is original and represents the spirit of his time, namely the hyperrealism style.